Exploring the Pancasila Values in the English Writing Teaching Materials Made by Microteaching Student - Sa’dhiyah, Kholifatus (FKIP Universitas Islam Jember, 2024)
In Indonesia, the education curriculum underwent significant changes with the introduction of the Independent Curriculum. Meanwhile, curriculum changes have not been followed by the development of adequate teaching materials. Researchers conducted an analysis of English writing teaching materials for junior high school documents made by microteaching students. This research aims to identify how Pancasila values are integrated into English writing teaching materials created by micro-teaching students of the English Department for use in the independent curriculum. The research design in this study used qualitative and content analysis. The data collection method uses content analysis with the Miles and Huberman model approach. The findings of this research reveal that the English writing teaching materials developed by microteaching students at a university in Indonesia for junior high school effectively embody Pancasila values, making them appropriate for implementation in the independent curriculum.